Variation over time of the Perez calibration algorithm for ground-based spectrometer - Chin, Su Na; Natalie Vanessa Boyou; Rubena Binti Yusoff; Ag. Sufiyan Abd. Hamid; Fauziah Sulaiman; Jedol Dayou (2016)
A spectrometer is likely to perform as expected over a period of time if calibrated with suitable method. This paper aims to study the variation of the Perez calibration algorithm over time for a spectrometer. The study was carried out for six months from July to August 2012 and January–April 2013. The measurements were recorded for every minute interval from 8.30 a.m. to 4.30 p.m. in three locations in Kota Kinabalu, Sabah, Malaysia. Monthly calibration constants for eight wavelengths were determined for the Perez model using improved Langley method. When only wavelengths which are close to 500 nm (460, 500, 540, 580, and 620 nm) were engaged, the variations over time of the Perez calibration constants were consistent over time (F = 1:381, p = 0:273). This is similar to the previous ?nding on the Du Mortier algorithm.